Measurement of prompt charged-particle production in pp collisions at √s = 13 TeV - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Frau, Giulia; Gerick, David; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; et al. (Journal of high energy physics, 2022)
The differential cross-section of prompt inclusive production of long-lived charged particles in proton-proton collisions is measured using a data sample recorded by the LHCb experiment at a centre-of-mass energy of √s = 13 TeV. The data sample, collected with an unbiased trigger, corresponds to an integrated luminosity of 5.4 nb−1. The differential cross-section is measured as a function of transverse momentum and pseudorapidity in the ranges pT ∈ [80, 10 000) MeV/c and η ∈ [2.0, 4.8) and is determined separately for positively and negatively charged particles. The results are compared with predictions from various hadronic-interaction models.
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
The LHCb collaboration: R. Aaij, F. Archilli, S. Bachmann, D. Berninghoff, M. Borsato, G. Frau, D. Gerick, J.P. Grabowski, P.A. Günther, X. Han, S. Hansmann-Menzemer, J. Hu, R. Kopecná, B. Leverington, P. Li, J. Marks, N. Meinert, D.J. Unverzagt, U. Uwer, H. Viemann, L. Witola, A. Zhelezov [und viele weitere]
Gesehen am 07.10.2022